Customization of 433 MHz Antenna for an ISM Application using Meanderline Structure - Surahmat, Indar (Journal of Electrical Technology UMY, 2017)
Innovation on ISM devices has been an interensting trend in roboticsÂ application. Antenna as a wireless interfacing part in communication between the device and another requires a specific design to fit an available space in the device. This paperexplores a customized design of 433MHz antenna for an application of ISM devices.Antenna is designed by using meandeline structure theory. An antenna for the frequency has been simulated and fabricated. The design is implemented in 38mm x 110mm FR-4 PCB with thickness 1.6mm. The antenna has a maximum gain 1.1 dB and SWR 1.83 at the frequency.